Analisis Naratif Respons Emosional Orang Tua Pascadiagnosis Anak Berkebutuhan Khusus - Bastiana, Bastiana; Syamsuddin, Syamsuddin; Faizal , Faizal; Sulasminah, Dwiyatmi (Transpublika Publisher, 2025)
Parents of children with special needs (CSN) frequently experience intense emotional turmoil following their child's diagnosis. This qualitative study examines the transformation of parents' emotional responses before and after participating in a psychoeducational seminar titled